1952 - 2nd 'Homecoming' - Queen and Princesses - James Tanji::::::photographer::: (1952)
Group portrait of 5 female students, seated on a lawn in front of a California Polytechnic building. The students are (not in order from left-right): Janice Mehl, Janet Shields, Queen Louise, Marty Bell, and Gay Casey.